Mediastinal and subcutaneous emphysema after manual strangulation - Onur Bayrakçı,; Sevinç Yağcı,; Ahmet Uluşan,; Maruf Şanlı, (Indian Journal of Case Reports, 2021)
Pneumomediastinum is a disease characterized by the presence of air in the mediastinum. The disease is examined in two categories as spontaneous and secondary and frequently seen as a result of traumatic causes. In our study, we present a case of diffuse mediastinal and subcutaneous emphysema after strangulation, unrelated to penetrating injury. After detailed anamnesis, it was understood that it was not a simple penetrating injury but a complicated trauma. Anamnesis, clinical findings, and radiology should be compatible with each other. When necessary, detailed anamnesis should be insisted and the etiology of blunt trauma should be investigated, especially if mediastinal emphysema is detected. Complications such as tension pneumomediastinum, pneumopericardium, and mediastinitis can be seen which complicates the disease and can result in death.